Terminal Imido Complexes of the Groups 9–11: Electronic Structure and Developments in the Last Decade - Grünwald, Annette; Anjana, S. S.; Munz, Dominik (European Journal of Inorganic Chemistry, 2021)
We thank the Fonds der Chemischen Industrie (Liebig fellowship for D.M.), the German-American Fulbright Commission (Fulbright-Cottrell Award for D.M.) as well as the Bavarian Equal Opportunities Sponsorship – Realization of Equal Opportunities for Women in Research and Teaching (fellowship for A.G.) for financial support. We thank the RRZ Erlangen for computational resources.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Electronic structure; Imido ligands; Late transition metals; Multiple bonds; Nitrene ligands